From Santander to Camilo and Ché: Graffiti and Resistance in Contemporary Colombia - Benavides Vanegas, Farid Samir (Social justice, 2005)
Part of a special issue on emerging imaginaries of regulation, control, and repression. The writer analyzes the symbolic nature of the use of images of Camilo Torres and Ernesto “Ché” Guevara—the former a priest who was assassinated fighting for the liberty of Colombians and all oppressed people, the latter an Argentinean guerrillero who died in Bolivia—in graffiti on the walls at the Universidad Nacional de Colombia, Bogota. He discusses the reasons why students used the symbols of two failed revolutionaries to demonstrate their opposition to the government and the guerrilla movements and why they altered the name of the campus's central square to Plaza “Ché” Guevara. He suggests that the graffiti and the renaming of the square express an imaginary of resistance in which murals have become a new mode of quiet social mobilization.